The burdens of participation: A mixed-methods study of the effects of a nutrition-sensitive agriculture program on women’s time use in Malawi - Margolies, Amy; Colantuoni, Elizabeth; Morgan, Rosemary; Gelli, Aulo; Caulfield, Laura E. (Elsevier, 2023)
Development programs often rely on women’s participation. However, there is little evidence of whether development programs that engage women’s unpaid labor – particularly in care work – add to their time burdens. We tested this hypothesis on a nutrition-sensitive agriculture program delivered through community-based preschools in Malawi. The mixed-methods study was conducted over one year using data from 1,168 female caregivers from a cluster-randomized control trial. A longitudinal binomial logistic regression model was used to estimate the proportion of time spent caregiving in a 24-hour period (expressed as minutes) at baseline and then separately for each treatment group at 6-months and 1-year post-randomization. In addition, two rounds of 38 qualitative in-depth interviews (n = 76) were conducted with women, men and adolescent girls to explore their perceptions of program activities, time use and gender attitudes. We found that the program quantitatively increased daily caregiving time for participating women by approximately 30 min. However, this effect occurred only during the lean season when preschool scale-up investments increased. Qualitatively, program-related tasks were not considered burdensome. Moreover, participants saw contributions as important investments in their children’s development. These findings add to limited evidence of the impacts of nutrition-sensitive agricultural programs and early childhood interventions on women’s time use. Measuring women’s participation through mixed-method evaluations can aid interpretation to avoid harm and to better understand the tradeoffs of women’s time.